2016
DOI: 10.18632/oncotarget.11418
|View full text |Cite
|
Sign up to set email alerts
|

Application of PET/CT in treatment response evaluation and recurrence prediction in patients with newly-diagnosed multiple myeloma

Abstract: Multiple myeloma (MM) causes osteolytic lesions which can be detected by 18F-fluorodeoxyglucose positron emission tomography/Computed tomography (18F-FDG PET/CT). We prospectively involve 96 Newly diagnosed MM to take PET/CT scan at scheduled treatment time (figure 1), and 18F-FDG uptake of lesion was measured by SUVmax and T/Mmax. All MM patients took bortezomib based chemotherapy as induction and received ASCT and maintenance. All clinical features were analyzed with the PET/CT image changes, and some relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 21 publications
1
5
0
1
Order By: Relevance
“…Indeed, independently from response, Bortezomib increased [ 18 F]FDG uptake and volume of distribution, whereas [ 18 F]4-FGln parameters were more closely associated with the response, suggesting that [ 18 F]4-FGln based PET scan reliably delineates tumor sensitivity to the drug. In line with our observations, it has been reported that [ 18 F]FDG uptake may persist in MM patients who achieved complete response to Bortezomib (37). The drug has been reported to stimulate aerobic glycolysis, thus possibly indicating that changes in tumor volume are masked by increased glycolytic flux (38)(39)(40).…”
Section: F]fdg In Extramedullary Lesion Insupporting
confidence: 91%
“…Indeed, independently from response, Bortezomib increased [ 18 F]FDG uptake and volume of distribution, whereas [ 18 F]4-FGln parameters were more closely associated with the response, suggesting that [ 18 F]4-FGln based PET scan reliably delineates tumor sensitivity to the drug. In line with our observations, it has been reported that [ 18 F]FDG uptake may persist in MM patients who achieved complete response to Bortezomib (37). The drug has been reported to stimulate aerobic glycolysis, thus possibly indicating that changes in tumor volume are masked by increased glycolytic flux (38)(39)(40).…”
Section: F]fdg In Extramedullary Lesion Insupporting
confidence: 91%
“…They also revealed the correlation between FDG uptake and some prognostically relevant laboratory parameters such as β2M and CRP [35]. As well the correlation between SUVmax in bone lesions and clinical parameters related to tumor burden such as high M protein, plasma cell >20% in bone marrow, β2M>3.5mg/dl, hypercalcemia at the onset of disease, and increased LDH was reported by Li et al [36].…”
Section: The Role Of Pet/ct In the Assessment Of Prognosismentioning
confidence: 56%
“…Previous studies reported a correlation between FDG uptake by BM and PC in ltration [12,20,28,29,[42][43][44][45], while others showed that FDG uptake correlated with b2m [28,29] and CRP (29) and negatively correlated with Hb and HT [29] as well as Alb [28].…”
Section: Discussionmentioning
confidence: 96%